Contribution of Household Sanitation to Acute Respiratory Infection Symptoms Among Children: Analysis of the 2017 Indonesian Demographic Health Survey - Iswanto Iswanto; Sepsiana Puspitasari; Windu Syawalina Wahyuningsih; Nurendah Ratri Azhar Rusprayunita; Furaida Khasanah; Indira Puspa Febryanti (JURNAL INFO KESEHATAN, 2025)
Acute Respiratory Infections  (ARI) remain one of the primary causes of mortality among children under 5 in Indonesia, and poor inadequate drinking water, sanitation, and hygiene (WASH) conditions can exacerbated the transmission of respiratory pathogens. However, their association with ARIs in Indonesia remains underreported. This study aimed to analyze the contribution of these sanitation conditions to ARI symptoms in children under five in Indonesia. This research method was cross-sectional quantitative design study based on secondary data from the 2017 Indonesian Demographic and Health Survey (IDHS), based on secondary data from the 2017 Indonesian Demographic and Health Survey (IDHS), which was the most recent available at the time of the study. The determined sample consisted all toddlers aged 0-59 months, from women aged 15-49 years. The weighted sample that met the inclusion criteria (children aged 0-59 months, living with their parents, willing to answer questions) and exclusion criteria (missing data and "don't know" answers) consisted of 16,681 observations. Independent variables included sanitation infrastructure, mother’s education, wealth index, and residential location. The dependent variable was reported ARI symptoms in 2 weeks prior to the interview by their mother. Data were analyzed using CI 95% logistic regression to determine associations, and pathway analysis was conducted to explore the direct and indirect relationships among variables. Poor toilet facilities [OR: 1.80, CI: 1.46-2,27] increased the risk of ARI symptom, meanwhile treated water before consumption reduce the risk [OR:0.63, CI:0.51-0.77]. Long travel distances to clean water aslo were found as factor that increased the risk of ARI symptoms [OR:2.31, CI:0.65-3.02]. Indirect factors such as low mother’s education, low wealth index, and rural residency, also contributed to ARI symptoms in children. In conclusion, inadequate household sanitation significantly contribute to ARI symptoms in children under five in Indonesia. These findings underscore the need for improved sanitation infrastructure and targeted health interventions in vulnerable communities.